Information Networking. Towards Ubiquitous Networking and Services: International Conference, ICOIN 2007, Estoril, Portugal, January 23-25, 2007. Revised Selected Papers - Hutchison, David; Kanade, Takeo; Kittler, Josef (Lecture Notes in Computer Science, 2008)
This volume contains the set of revised selected papers presented at the 21st International Conference on Information Networking (ICOIN 2007), which was held in Estoril, Portugal, January 23-25, 2007. The conference series started under the name of Joint Workshop on Computer Communications, in 1986. At that time, it constituted a technical meeting for researchersand engineers on - ternet technologies in East Asian countries, where several technical networking issues were discussed. In 1993, the meeting was reorganized as an international conference known as ICOIN. Recent conferences were held in Sendai, Japan (2006),Jeju,Korea(2005),Pusan,Korea(2004),Jeju,Korea(2003),Jeju,Korea (2002), Beppu City, Japan (2001), Hsin-chu, Taiwan (2000), and Tokyo, Japan (1999). In 2007, for the ?rst time since its creation, ICOIN took place outside Asia, and we were very pleased to host it in Portugal. ICOIN 2007 was or- nized by INESC-ID and IST/Technical University of Lisbon (Portugal) with the technical co-sponsorship of IEEE Communications Society and IEEE Portugal Section-Computer Society Chapter, in cooperation with the Order of Engineers CollegeofInformaticsEngineering(Portugal),IPSJ(InformationProcessing- ciety of Japan), KISS (Korea Information Science Society), and Lecture Notes in Computer Science (LNCS), Springer, Germany. The papers presented in this volume were selected in two stages: 1) revi- ing and selection for the ICOIN program and 2) on-site presentation review by session chairs or by program committee chairs.